2017
DOI: 10.1080/19440049.2017.1364433
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic dietary exposure to ethyl carbamate from fermented foods and alcoholic beverages in the Korean population

Abstract: The occurrence of ethyl carbamate was investigated in fermented foods and alcoholic beverages of the Korean total diet study. The concentrations of ethyl carbamate ranged from not detected to 166.5 μg kg. Dietary exposure to ethyl carbamate was estimated by the probabilistic method. Estimated intakes of ethyl carbamate from foods and alcoholic beverages were 4.12 ng kg body weight (bw) per day for average consumers and 12.37 ng kg bw/day for 95th percentile high consumers. The major foods contributing to ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Koh and Kwon reported that the maximum EC content in Japanese-style soy sauce reached 128.9 μg/L [5]. Soy sauce has become the most remarkable source of EC exposure in some Asian countries due to its high consumption, especially among children [6,7]. Therefore, the presence of EC in soy sauce should be controlled to the lowest level with a feasible technical approach, and this control hinges on a full understanding of the formation of EC.…”
Section: Introductionmentioning
confidence: 99%
“…Koh and Kwon reported that the maximum EC content in Japanese-style soy sauce reached 128.9 μg/L [5]. Soy sauce has become the most remarkable source of EC exposure in some Asian countries due to its high consumption, especially among children [6,7]. Therefore, the presence of EC in soy sauce should be controlled to the lowest level with a feasible technical approach, and this control hinges on a full understanding of the formation of EC.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In addition, Lajovic et al demonstrated the carcinogenesis of vinyl carbamate epoxide, the ultimate carcinogen of EC metabolism, 22 through both experimentally and quantum chemical simulations. 23 Thus, many countries including Canada, 24 the USA, 25 Brazil, 26 and South Korea 27 have set a maximum residue level for EC in fermented beverages. Despite that high levels of EC are found in many regularly consumed Chinese alcoholic beverages, no In this work, transcriptome sequencing was performed to analyze the effects of musalais containing varying amounts of EC on gene expression in rat liver and kidney, the major organs involved in metabolism and detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is a product of lipid peroxidation in cell membranes. The level of MDA is indirectly used for evaluation of the degree of damage to cell membranes by free radical-induced lipid peroxidation [15]. Superoxide dismutase (SOD) is a relatively ubiquitous antioxidant enzyme in humans.…”
Section: Discussionmentioning
confidence: 99%